2018
DOI: 10.1088/1361-6587/aac7fe
|View full text |Cite
|
Sign up to set email alerts
|

Disruption prediction investigations using Machine Learning tools on DIII-D and Alcator C-Mod

Abstract: Using data-driven methodology, we exploit the time series of relevant plasma parameters for a large set of disrupted and non-disrupted discharges to develop a classification algorithm for detecting disruptive phases in shots that eventually disrupt. Comparing the same methodology on different devices is crucial in order to have information on the portability of the developed algorithm and the possible extrapolation to ITER. Therefore, we use data from two very different tokamaks, DIII-D and Alcator C-Mod. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
105
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(107 citation statements)
references
References 39 publications
2
105
0
Order By: Relevance
“…Disruption prediction on Alcator C-Mod has proven challenging (Rea et al. 2018; Montes et al. 2019) due to the high fraction of disruptions caused by molybdenum flecks; an event with an inherent time scale of the order of milliseconds.…”
Section: Disruption Statistics Mitigation and Predictionmentioning
confidence: 99%
“…Disruption prediction on Alcator C-Mod has proven challenging (Rea et al. 2018; Montes et al. 2019) due to the high fraction of disruptions caused by molybdenum flecks; an event with an inherent time scale of the order of milliseconds.…”
Section: Disruption Statistics Mitigation and Predictionmentioning
confidence: 99%
“…This method fully characterizes a resistive kink instability on a small time window, indicating the ability for robust data-driven identification of MHD instabilities, with implications for real-time control. These methods, with online training and communication with other machine learning techniques with offline training [51,60,61], could prove useful for disruption mitigation. If both the discovery of interpretable dynamics and the accurate characterization of instabilities is desired, the authors recommend a joint use of both the sparsity-promoting and optimized DMD algorithms, as illustrated here.…”
Section: Resultsmentioning
confidence: 99%
“…Predictions from machine learning models trained on large data sets have been employed in fusion energy research since the early-1990s. For example, Wroblewski et al [74] employed a neural network to predict high beta disruptions in real-time from many axisymmetric-only input signals, Windsor et al [72] produced a multi-machine applicable disruption predictor for JET and ASDEX-UG, Rea et al [61] and Montes et al [48] demonstrated use of time series data and explicit look-ahead time windows for disruption predictability in Alcator C-Mod, DIII-D, and EAST (see Fig. 11), and Kates-Harbeck [33] demonstrated use of extensive profile measurements in multi-machine disruption prediction for JET and DIII-D with convolutional and recurrent neural networks.…”
Section: Machine Learning Methodsmentioning
confidence: 99%